Hierarchical HRP-Crosslinked Silk Fibroin/ZnSr-TCP Scaffolds for Osteochondral Tissue Regeneration: Assessment of the Mechanical and Antibacterial Properties - Ribeiro, Viviana P.; Pina, Sandra; Gheduzzi, Sabina; Araújo, Ana C.; Reis, Rui L.; Oliveira, Joaquim M. (Frontiers in Materials, 2020)
The biomaterials requirements for osteochondral (OC) defects restoration simultaneously include adequate mechanical behavior, and the prevention of bacterial adherence and biofilm formation, without impairing local tissue integration. Bilayered and hierarchical scaffolds combining a cartilage-like layer interconnected to an underlying subchondral bone-like layer appeared as innovative technological solutions able to mimic the native OC tissue hierarchical architecture. This study is focused on the assessment of the combined compression-shear stresses and possible bacterial biofilm formation of hierarchical scaffolds prepared from a horseradish peroxidase (HRP)-crosslinking reaction of silk fibroin (SF) combined with zinc (Zn) and strontium (Sr)-doped β-tricalcium phosphate (β-TCP) for OC tissue regeneration. Scaffolds with undoped-β-TCP incorporation were used as control. Results showed that the bilayered scaffolds presented suitable aptitude to support compression and shear loading for OC tissue, with better mechanical properties for the ZnSr-containing structures. Young and shear moduli presented values close to 0.01 MPa in the region 10-20% strain. The investigation of biomaterials surface ability to prevent biofilm formation showed reduced bacterial adhesion of Escherichia coli (E. coli, gram-negative) and Staphylococcus aureus (S. aureus, gram-positive) on both scaffolds, thus suggesting that the proposed hierarchical scaffolds have a positive effect in preventing gram-positive and gram-negative bacteria proliferation.